Experience and Signaling Value in Technology Licensing Contract Payment Structures - Kotha, Reddi; Crama, Pascale; Kim, Phillip H. (Academy of Management Journal, 2018)
When commercializing technology, the lack of proven results and a reluctance to invest upfront in resources hamper efforts by firms to work jointly with inventors to bring new discoveries to market. An effective contract payment structure—a mix of upfront and royalty payments—can help overcome these hurdles. We conduct our research in university technology licensing, where licensing managers act as intermediaries to unite inventors and licensee firms. Rather than leveraging their experience to bargain for maximum payments, highly experienced managers offer contractual payment structures that trade lower upfront payments for higher royalty payments in order to signal value. The signal instills confidence in the value of the partnership for skeptical licensee firms, and experienced licensing managers can amplify signals as needed to overcome the uncertainties inherent in technology commercialization. By explicitly addressing these variations in signal strength, we develop new theory that builds on classical signaling principles. We test and confirm these predictions in a sample of over 950 invention-licensing contracts. In addition to advancing signaling theory, our work has implications for academic entrepreneurship, and for how experience shapes value-sharing agreements in collaborative innovations.